Pengembangan Bahan Ajar Realistic Mathematic Education Dengan Sistem Flipped Classroom Bagi Siswa Sekolah Dasar - Marcellyna Marcellyna; Desyandri Desyandri (Universitas Negeri Padang, 2022)
This research aims to develop speed teaching materials with the Flipped Classroom system using a Realistic Mathematical Education approach. The research method used is the ADDIE model including analysis, design, development, implementation, and evaluation. The teaching materials developed were analyzed by a team of experts. The research subjects were students of class V. Practically, teaching materials were seen from the content and objectives that were clear, easy to read, looked attractive, and could increase the attractiveness/interest of students to learn. The effectiveness of teaching materials is seen in the increase in student learning outcomes with a learning completeness rate of 96%. Based on these results, it can be concluded that speed teaching materials using a realistic mathematical education (RME) approach with the Flipped Classroom system developed for fifth-grade elementary school students are declared valid, practical, and effective.